The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1074/jbc.m110.141010
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 Activity Is Required for Mitotic Activation of Aurora A during G2/M Transition of Human Cells

Abstract: In mammalian cells entry into and progression through mitosis are regulated by multiple mitotic kinases. How mitotic kinases interact with each other and coordinately regulate mitosis remains to be fully understood. Here we employed a chemical biology approach using selective small molecule kinase inhibitors to dissect the relationship between Cdk1 and Aurora A kinases during G 2 /M transition. We find that activation of Aurora A first occurs at centrosomes at late G 2 and is required for centrosome separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 39 publications
4
61
2
Order By: Relevance
“…Only Aurora A has been shown to definitively require Cdk1/Cyclin B for activation during mitosis. 30 Second, Aurora A has been shown to act as a bona fide oncogene and induction of Bim degradation is consistent with this activity. Third, we observe that the Aurora A inhibitor MLN8054 prevents mitotic phosphorylation of BimEL on S93/94/98 and stabilizes the protein.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Only Aurora A has been shown to definitively require Cdk1/Cyclin B for activation during mitosis. 30 Second, Aurora A has been shown to act as a bona fide oncogene and induction of Bim degradation is consistent with this activity. Third, we observe that the Aurora A inhibitor MLN8054 prevents mitotic phosphorylation of BimEL on S93/94/98 and stabilizes the protein.…”
Section: Discussionmentioning
confidence: 84%
“…Intriguingly, mitotic activation of Aurora A has been shown to be dependent upon cdk1 activity. 30 We therefore determined if S93/94/98 is phosphorylated during mitosis by Aurora A. 293T cells were arrested using Thy/Noc and released into increasing concentrations of the Aurora kinase inhibitor MLN8054.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that aurora kinase A plays an important role in FGF8b-mediated cell proliferation but in its absence, proteins with redundant functions can overtake its actions. Plk1 might be one such protein as Aurora kinase A and Plk1 are shown to have redundant functions in activation of Cdk1 to promote entry into mitosis (Van Horn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We further identified that a function of BMP4 signaling can induce cyclin B1 and CDK1 overexpression in HCC cells. The complex kinase of cyclin B1 and CDK1 is an important mediator of the cell-cycle regulator, which accelerates the progress of mitosis (37)(38)(39). It was observed, through Ki-67 staining, that BMP4 triggered the synthesis of DNA, which is required for cell division, and promoted the phosphorylation of ser10 residue of histone3 known as a marker for mitotic progression (40).…”
Section: Discussionmentioning
confidence: 99%